THE DYNAMICS OF PESANTREN LEADERSHIP FROM THE DUTCH ETHICAL POLICY TO THE REFORMATION PERIODS - Auliya Ridwan (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2020)
In its early periods, pesantren as a type of Islamic educational institution focused merely on religious teachings. Socio-political pressures and the need to carry out Islamic outreach have pushed kiai as pesantren leaders to negotiate their idealism according to the circumstances in different historical periods. Historical accounts from the Dutch colonial period to Indonesian independence show that kiai leadership becomes the decisive factor as well as the legitimation for pesantren to take certain actions during precarious situations. To examine the institutional development of pesantren in the post-reformation era, a recent ethnographic fieldwork has been carried out in three pesantren in Madura, Java, and Lombok. This paper discusses the development and transformation of pesantren as an institution from the Dutch Ethical Policy Period until today. It demonstrates pesantren’s involvement in anti-Western campaigns and trials of affiliation with oppositions in the colonial period. This paper shows how Islamic virtues remain the heart of pesantren education and examines how innovation in contemporary pesantren regarding pedagogies and values translated in seemingly non-religious areas is substantially based on religious values.